UPAYA PENEGAKAN HUKUM ATAS TERJADINYA TRANSAKSI FIKTIF PERBANKAN OLEH TELLER BANK BRI KEPADA NASABAH - Muhammad Wildan Ichsandi; Gurnadi Lie; Moody R. Syailendra (LPPM Universitas Ekasakti Padang, 2023)
This study aims to analyse the form of law enforcement on the occurrence of fictitious banking transactions by BRI Bank tellers to customers conducted by bank employees, to find out the form of violations. Analyse the form of law enforcement to banking tellers related to fictitious transactions. This research is a normative legal research. Forms of law enforcement on the occurrence of fictitious banking transactions by BRI Bank tellers to customers. Fictitious transactions (false records) carried out by bank employees are carried out in 2 (two) ways, namely implicitly (Implicit Protection) and explicitly (Expliciti Protection). Implicitly carried out by the bank's own internal policies and responsibilities in carrying out banking activities, and at the same time explicitly carried out through the supervisory means of Bank Indonesia to control and supervise every banking activity of commercial banks. Normatively, legal protection against fictitious transactions is based on Law Number 7 of 1992 concerning Banking. then accommodated also by Law Number 3 of 2004 concerning Amendments to Law Number 23 of 1999 concerning Bank Indonesia and for customer deposit funds regulated under Law Number 24 of 2004 concerning the Deposit Insurance Corporation and also regulated in relation to implementation guidelines through Bank Indonesia Regulations. Law Enforcement to BRI Bank tellers due to fictitious transactions is carried out implicitly and explicitly. Implicitly, namely by imposing administrative sanctions from the bank in the form of Termination of Employment (PHK) to the perpetrator with the initials SAP as a BRI Bank teller and besides that, it is also carried out explicitly in the form of punishment against the suspect with the initials SAP charged with Articles 2 and 3 of Law No. 31 of 1999 concerning Corruption with a penalty of 20 years in prison.